Strategic Insights and Practical Tips for Establishing the Aseptic Chemotherapy Drug Compounding Unit in a Tehran Hospital: A Comprehensive Guide to Operational Success (Journal of Medical Device Technology, 2024)
Aseptic compounding units are critical in the pharmaceutical field, especially for handling hazardous medications like chemotherapy drugs. These facilities are crucial for safeguarding patients, healthcare workers, and the environment. This article presents a practical roadmap for institutions seeking to establish chemotherapy drug preparation centers, drawing upon the experience of Iran's first GMP-compliant drug preparation unit. It delves into the regulatory framework, encompassing compliance with international standards like USP797 and USP800, and outlines the essential steps involved, including physical space establishment, clean room construction, human resource management, communication protocols, standard operating procedures, documentation, and authorization processes. The article emphasizes the paramount importance of patient safety, personnel safety, and environmental safety, highlighting the risks associated with hazardous drugs and the need for robust protective measures and protocols. It also acknowledges the challenges faced in Iran, including equipment accessibility and adherence to standards, and underscores the urgency for addressing these issues. The article concludes by advocating for the rapid establishment and development of drug preparation units in chemotherapy facilities across Iran, drawing inspiration from the successful implementation of the first GMP-compliant center and advocating for greater legislative support and collaboration.
Keywords: Aseptic compounding units; Chemotherapy drug preparation centers; Good Manufacturing Practices (GMP); Patient safety; Hazardous drugs